Pb(II) removal in water via adsorption onto deep eutectic solvent fabricated activated carbon - Pam, Aloysius Akaangee; Mohd Hir, Zul Adlan; Abdullah, Abdul Halim; Tan, Yen Ping (Springer, 2021)
In our current work, we have established a novel approach in the synthesis of a new adsorbent by using choline chloride and urea (DES)/orthophosphoric acid (H3PO4) as our activating agent and palm kernel shell (PKS) as our precursor. The resulting activated carbon (DES/H3PO4-6002:3) was used to adsorb Pb(II) from aqueous solution. Characterization of DES-H3PO4-6002:3 by nitrogen adsorption/desorption isotherm measurements, scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA) demonstrated good micropores structure and high surface area that makes DES/H3PO4-600 2:3 a suitable alternative for liquid phase adsorption. The fundamental batch experiment of DES/H3PO4-600 2:3 was investigated by different parameters (such as concentration, pH, temperature and absorbent dose). The results obtained indicated that Langmuir model and pseudo-second-order equation best fit the data, indicating that the adsorption was controlled by chemical reaction and monolayer uptake. In addition, the fabrication of DES/H3PO4 AC exhibits good potential for Pb(II) ions uptake, including its high adsorption capacity (97.1 mg/g) and good recyclability. The future potential of this works lies in the identification of alternatives to environmental benign synthesis AC and reuse of Pb(II) ion–laden biosorbent after heavy metal uptake.